2004
DOI: 10.1080/02678290410001675156
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour of the thermotropic cubic mesogen 1,2-bis(4-n-decyloxybenzoyl)hydrazine under pressure

Abstract: The phase transition behaviour of an optically isotropic, thermotropic cubic mesogen 1,2-bis(4-n-decyloxybenzoyl)hydrazine, BABH(10), was investigated under pressures up to 300 MPa using a high pressure differential thermal analyser, a wide angle X-ray diffractometer and a polarizing optical microscope (POM) equipped with a high pressure optical cell. The reversible change in structure and optical texture between the cubic (Cub) and smectic C (SmC) phases was associated with a change from a spot-like X-ray pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Figure 2 shows the X-ray pattern of the cubic phase of BABH (12) at 150 ‡C in the cooling mode at atmospheric pressure. The spotlike reflections indicate a polydomain structure, as already seen for the cubic phases of BABH(8) and BABH(10) [25,26]. The pattern of diffraction spots of the cubic phase is very similar to that for BABH (8) which reduced to the {2 1 1} and {2 2 0} reflections of the cubic phase with space group Ia3d [16].…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Figure 2 shows the X-ray pattern of the cubic phase of BABH (12) at 150 ‡C in the cooling mode at atmospheric pressure. The spotlike reflections indicate a polydomain structure, as already seen for the cubic phases of BABH(8) and BABH(10) [25,26]. The pattern of diffraction spots of the cubic phase is very similar to that for BABH (8) which reduced to the {2 1 1} and {2 2 0} reflections of the cubic phase with space group Ia3d [16].…”
Section: Resultsmentioning
confidence: 56%
“…This clearly reveals the pressure-induced formation of the SmC phase and is the same texture as observed in BABH(8) and BABH(10) [25,26]. The bright islands grow rapidly with decreasing temperature, figures 7 (c) and 7 (d ), and coalesce to form the homogeneous sand-like texture of the SmC phase at 157 ‡C, figure 7 (e), although small black spots randomly placed of the cubic phase remain.…”
Section: Morphological and Structural Observations Undermentioning
confidence: 50%
See 2 more Smart Citations
“…35 Maeda et al also reported that the spotty ring patterns are observed from the space group Ia3d of the bicontinuous cubic phase. 36 Although no clear sharp peak was observed in the diffractogram (see Figure 3b, left-hand side), the reciprocal spacings of the first and second Bragg peaks were found to be in the ratio 6:…”
Section: Binary Mel-a/water Phase Diagram At Roommentioning
confidence: 93%